Collaboration Between Agricultural Extension Center and Village Government in Developing Farmers' Groups in Rahanggada Village, Tanggetada District, Kolaka Regency - Ni Nyoman Tri Sudani; Achmad Lamo Said; Sudirman Baso (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
The problem lies in the lack of mentoring and empowerment for farmer groups in Rahanggada Village, resulting in low productivity, minimal use of technology, and limited access to training or empowerment initiatives. The purpose of this study is to identify and analyze the collaboration process between the Agricultural Extension Center (BPP) and the Village Government in an effort to develop farmer groups in the Rahanggada Village area. The research method used is qualitative with a descriptive and narrative approach. Data were collected through in-depth interviews, field observations, and document analysis with informants from the Agricultural Extension Center (BPP), the Village Government, and Farmer Groups. Analysis techniques include data reduction, data presentation, and drawing conclusions. The results indicate that, in general, this collaboration has managed to build good trust between actors, as well as strong mutual understanding and commitment to the process from both parties, which has resulted in temporary impacts, namely the smooth distribution of seeds, fertilizers, and pesticide aid to farmer groups. However, the effectiveness of this collaboration is not yet optimal because face-to-face dialogue faces structural obstacles, such as high administrative workloads between Agricultural Extension Officers and the Village Government; consequently, training and empowerment efforts in developing farmer groups are not optimally implemented. To mitigate these obstacles, it is hoped that in the future, the intensity of physical interactions can be increased to optimize technical training and empowerment.